Studying the role of staphyloxanthin in modulating membrane structural parameters in DMPG and DPPG lipid bilayers (2018)
Molecular dynamics provide a way of studying the dynamics of lipid bilayers with atomistic resolution. This has enabled biophysicist to explore atomic effects and give more detailed explanations to phenomena seen in laboratories. In recent years, a particular topic relating Staphylococcus aureus and resistance to cationic amphiphilic drugs has been the main priority of various research groups. Staphyloxanthin a membrane-bound carotenoid produced by Staphylococcus aureus appears to change mechanical properties of the bacterial membrane and thus impeding the normal interaction of antibiotics that target the membrane. Although it is known that a high concentration of staphyloxanthin increases membrane rigidity, the exact mechanism to this phenomena is not fully understood. In this thesis, we investigate the effect of staphyloxanthin in two single component lipid model membranes composed of 1,2-Dimyristoyl-phosphatidyl-glycerol (DMPG) and 1,2-Dipalmitoyl-phosphatidyl-glycerol (DPPG). We explore the membrane fluidity by assessing the order parameter of the acyl chains, the lateral diffusion and the local area per lipid. Surprisingly, we found that the orientation of the carotenoid tail in respect to the membrane normal acquired two drastically different conformations horizontal ({theta} ? 120) and vertical ({theta} ? 120). For the DMPG system the horizontal conformation was sampled for the majority of the simulated time, and for the DPPG system, the sampling of the conformations was distributed in a bimodal manner. For the vertical conformation we observed an increase in the order parameter for both bilayers as well as a decrease in the lateral diffusion coefficient solely for the DPPG bilayer, this showed a direct relationship with the area per lipid. For the horizontal similar changes were observed for the area per lipid and the order parameter.